The Effects of Cynara scolymus L. Leaf and Cichorium intybus L. Root Extracts on Carbon Tetrachloride Induced Liver Toxicity in Rats - H Fallah Huseini; A Zareei Mahmoudabady; SA Ziai; M Mehrazma; SM Alavian; M Mehdizadeh; T Radjabian (Institue of Medicinal Plants, ACECR, 2011)
Background: Cynara scolymus and Cichorium intybus are popular herbal remedy in folk medicine for liver disorders. Although many experimental studies carried out, scientifically reliable data needed to verify minimum effective dosage and efficacy of these medicinal plants. Objective: In present investigation, the effects of C. scolymus leaf and C. intybus root extracts at different doses were tested against CCl4 induced rats liver toxicity. Methods: The C. scolymus leaf and C. intybus root extracts at the doses of 300, 600 and 900 and 150, 300 and 450 mg/kg/day were prepared respectively. Liver intoxication was induced in 7 groups of rats by intraperitoneal injection of 1 ml/kg of 1:1 CCl4 in olive oil for two successive days. One group kept as control and six different doses of plant extracts were administered to six groups simultaneously with CCl4 administration. The serum levels of ALT, AST and ALP, liver tissue glutathione and catalase activity as well as liver tissue microvesicular steatosis (MVS) and pericentral coagulation necrosis (PCN) were determined after three days. Results: The serum ALT, AST and ALP and liver tissue MVS were significantly reduced in both the C. scolymus and C. intybus groups at the doses of 900 and 450 mg/kg/day respectively while liver tissue PCN significantly reduced in C. scolymus 900 mg/kg/day group only as compared to control group. Conclusion: In present study administration of the C. scolymus leaf (900 mg/kg/day) and C. intybus root (450 mg/kg/day) extracts ameliorated CCl4 induced rat serum liver enzyme changes and liver tissue histopathological damage.